A Feasibility Study on the Establishment of Frittes N' Vergs in Brgy. San Bartolome Quezon City (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
The problem of today’s society is that people are so busy and tend not to eat every time they go to work, for the reason that they do not have enough time to cook for themselves. Some people want to buy foods from fast foods because it is faster than homemade foods. Many people may not good at cooking and they prefer to buy foods than to cook their own. The researchers wanted to contribute something about this problem. Through persistence and determination, they come up to an idea of establishing a type of business that can save time and affordable. The method used to identify the problem was through a survey with 50 respondents. The researchers asked and distributed a list of questions to the respondents. The proponents encountered some problems while conducting a survey. One of these is the less participation of the people on the survey. The data gathered were collected and analyzed by the researchers for the purpose of a business proposal. The data gathered gave ideas to the researcher’s that the business had a great chance to become successful in the food industry. These gave assurance that the food will be loved by future customers. The ideas suggested by the respondents for the improvement of the product were noted by the researchers and included them for the next production. This research was conducted to know the viability of a business in a place where there are existing competitors. Based on observation, burgers and fries never go out of date because it can be added with a lot of twists and follow the trends of the masses. High numbers of young adult men and women have time-related beliefs and behaviors, such as being too rushed for breakfast, eating on the run, and perceiving that they did not have time to eat. It had been observed that, majority preferably ate on Frittes N’ Vergs, than in fast food on restaurants. The researchers believed that the adventures nature of the Filipinos submits themselves to learn new ideas and skills in this kind of business.
Keywords: Frittes N’ Vergs, San Bartolome, Quezon City Edsa